(untitled) (Jurnal Penelitian, 2024)
This article is intended to see the politicization of religion as a political ideology, as well as examines the use of communism discourse which is often used as issues to represent certain individuals, groups and relationships in Indonesia. The method used is a qualitative method, through searching data from the internet, television and other media regarding political religious discourse that developed in Indonesia through the 2019 election. The data was analyzed with discourse analysis of the models of Althusser and Faucoult. This study concludes that the politicization of religion and discourse of communism are still interesting issues in the political stage approaching general election of 2019. Discourse is used by certain parties as a way of communicating their purposes to attract attention, create images, divide public opinion, and eventually as a channel to build political legitimacy.